Classroom Behavior Management Chart - Alaarmi, Ali (My University, 2019)
This paper will discuss effective classroom behavior management in Saudi Arabia. For the purpose of this study, behavior management is defined as the tools that teachers use to keep students focused on learning, highly engaged and productive. Creative behavior management is important because without it, teachers waste their time and effort on correcting behavior and not on teaching. Good classroom management prevents disruptive behavior and helps teachers address behavior issues when they happen. 21st century classrooms are different because they rely on collaborative learning more than lecture learning. So, we should take into account as teachers, that collaborative learning requires other tools and rules to be followed by 21st century students. Studies have shown that using a visual classroom behavior management chart is an effective way to manage 21st century classrooms, because it takes into account six essential elements (Discussion, Support, Activity, Movement, Engagement, Success) in order to accomplish success in the learning. There are many strategies for using classroom behavior management charts to reduce classroom disruptions and office referrals, improve classroom climate, increase student on-task behavior and establish respectful and civil interactions. The key benefits of using classroom behavior management charts are teachers establish clear expectations with logical and fair responses to misbehavior, teachers spend less time disciplining and more time teaching, teachers learn tools to motivate students to do their best, and students are taught how to behave responsibly. This study involved training students at the beginning of the school year to educate them about behavior expectations and the positive relationship between good behavior and learning. In this project, behavior expectations will be presented to students on posters and reviewed by the teacher frequently. The anticipated success and improved learning in the classroom will be determined after one semester of implementation.
Keywords: Classroom; Behavior; Management Chart